2015
DOI: 10.7196/sajch.740
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of determining the position of an endotracheal tube in neonates by using bedside ultrasonography compared with chest radiographs

Abstract: Background. Neonates in our neonatal intensive care unit (NICU) receive a large amount of radiation with X-rays (XRs) being done daily, even more often with reintubation, repositioning of endotracheal tubes (ETTs) and confirmation thereof, which has been our NICU policy for many years. Objective. To investigate the feasibility of determining the position of ETTs in neonates by using bedside ultrasonography (BUS), and to compare the results with those obtained from chest XR (CXR) findings. Methods. A prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 12 publications
0
24
0
7
Order By: Relevance
“…10 Most subsequent studies reported manipulating the head and neck slightly for better US image acquisition. [11][12][13][14] Sethi et al and Dennington et al also oscillated the ETT to aid visualization and did not report adverse events. 11,12 Concerned about the potential risks of oscillating the ETT, Lingle tried using an US "standoff pad" over the infant's chest and neck instead and reported that it facilitated visualization and minimized handling 15 ; however, further studies have not evaluated this technique.…”
Section: Imaging Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…10 Most subsequent studies reported manipulating the head and neck slightly for better US image acquisition. [11][12][13][14] Sethi et al and Dennington et al also oscillated the ETT to aid visualization and did not report adverse events. 11,12 Concerned about the potential risks of oscillating the ETT, Lingle tried using an US "standoff pad" over the infant's chest and neck instead and reported that it facilitated visualization and minimized handling 15 ; however, further studies have not evaluated this technique.…”
Section: Imaging Techniquementioning
confidence: 99%
“…Slovis and Poland established the close correlation between the aortic arch on US and the carina on XR that has been used and verified in most of the subsequent studies. 10,12,16 The majority of authors concurred that optimal ETT placement as seen on US is between 1 and 1.5 cm above the aortic arch, 10,11,14,17 though one study concluded optimal ETT tip-to-aorta distance to be < 1 cm. 16 Dennington et al chose the superior portion of the right pulmonary artery as the US anatomic equivalent of the carina and their landmark for measuring ETT depth; the group reported 100% US-XR concordance.…”
Section: Imaging Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, ETT placement should be checked at the bedside using a method that is fast, noninvasive, reliable, tolerable, easy to learn and use, and without any need for radiation. Different methods are currently employed for this purpose, including the following: • clinical tests: thoracic auscultation and assessment of thoracic excursion, clinical signs (heart rate and oxygen saturation), presence of condensation in the tube, absence of stomach distension, and palpation of the ETT at the suprasternal notch; • direct laryngoscopy, which requires an expert operator and involves a temporary interruption of resuscitation maneuvers; • measuring end-tidal CO 2 (etCO 2 ) using a colorimetric method (recommended by the 2020 neonatal resuscitation guidelines [3]); this method can confirm whether the ETT is in the airways but cannot rule out a bronchial intubation or confirm the correct distance from the carina and glottis; • chest X-ray (CXR), which is currently the most often used method, but it is time-consuming, involves exposure to radiation, and is not always readily available in an emergency setting, and esophageal intubations may also occasionally be misinterpreted on a single anteroposterior scan; • ultrasound (US), a method still little investigated in clinical practice, but with promising results; it can be done using different acoustic windows (pulmonary US, diaphragmatic US, tracheal US, and suprasternal US in the sagittal position) [1,4] and different markers (aortic arch [5,6], aortic arch combined with thyroid [7], and right pulmonary artery (RPA) [8,9]. US is increasingly used every day in neonatology.…”
mentioning
confidence: 99%
“…Most of them demonstrated no statistically signi cant differences between the US and CXR in identifying the correct ETT position (2, 9, 10, and 11) nevertheless de Kock et al showed there was poor agreement between ndings of CXR and US (12) Our study results showed that bedside ultrasound had acceptable accuracy comparison to CXR for detecting the correct position of ETT in the neonate and also, was the faster and safer method than CXR with no complication during performance.…”
Section: Discussionmentioning
confidence: 47%